STUDI KOMPARATIF CENDIKIAWAN MUSLIM KLASIK DAN KONTEMPROR DALAM PEMBENTUKAN KONSEP DAN PRINSIP MAQASID AL-SYARIAH - Ahmad Burhanuddin; Sawaluddin Siregar (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2024)
. This study will analyze the methodology used by classical Islamic scholars in determining the concept and principles of maqāṣid alshariah. This analysis will compare the method of determining Maqasid Shariah by Muslim scholars with current scientific research methods. This research uses qualitative methodology by reviewing classical and modern scientific writings. The collected data is analyzed thematically based on inductive approach. The results of this study show that the formulation of the concept and principles of Maqasid Sharia involves the analysis of textual commands. The inductive reasoning of istiqrā' applied by Muslim scholars has similarities with thematic analysis in modern qualitative research. The results suggest basing ijtihad and fatwa on maqāṣid al-shariah through holistic textual analysis. This makes it possible to respond to new challenges through appropriate sharia laws by avoiding rigid legalism or unbridled rationalism.